Impact Assessment of Nutritional Supplement Program in Urban Settings: A study of under nutrition in Slum Community of Mumbai - Utkarsh Shah (Journal of Social and Development Sciences, 2011)
Malnutrition among 0-6 years is an impending problem, especially among economically backward communities in urban India. In an attempt to alleviate malnutrition, within the target community, the Foundation for Mother and Child, India, prepared a special food supplement, using cheap and locally available resources. A brief evaluation study was conducted to evaluate the impact of this food supplement on improvement in parameters like weight, height, and mental abilities among the participants. The study was conducted between August 2010 to October 2010 (n=51), with the participants divided in four different age groups. The height and weight parameters were compared to ICMR standards for the age to understand the impact of the program. The mean improvement in height was 0.84 cms (SD-0.6) while the mean improvement in weight was 0.57 kgs (SD-0.8). A significant variance was observed due to different consumption levels of the supplement and differing levels of under-nutrition. A strong correlation was observed between the consumption level and the improvement in height and weight parameters. In addition, a positive correlation was observed between the extent of deviation from ICMR standards and levels of improvement in height and weight parameters. No differential in terms of gender was observed within the community. No significant findings were observed with reference to improvement in mental ability, primarily as the study duration was short. The study has laid the roadmap for a larger and multifaceted study to be conducted to critically evaluate the effectiveness of the nutritional supplement.